2019
DOI: 10.1089/jwh.2018.6956
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Endometrial Cancer Following the Women's Health Initiative: An Assessment of Risk Factors

Abstract: Background: The Surveillance, Epidemiology, and End Result (SEER) database shows a variable increase in endometrial cancer incidence over time. The objective of this review was to examine published endometrial cancer rates and potential etiologies. Methods: Endometrial cancer incidence was obtained from the SEER Program database from 1975 through 2014, and a test for trend in incidence was calculated. Changes in risk factors thought to be associated with endometrial can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 73 publications
(62 reference statements)
3
92
0
Order By: Relevance
“…A recent study on the world-wide assessment of endometrial cancer and its risk factors revealed endometrial cancer as the sixth most common neoplasm in women [100]. This study documents remarkable increase in endometrial cancer (EC) in 26 of the 43 populations studied during 1978-2013.…”
Section: Endometriosis-associated Extra-ovarian Cancersmentioning
confidence: 58%
“…A recent study on the world-wide assessment of endometrial cancer and its risk factors revealed endometrial cancer as the sixth most common neoplasm in women [100]. This study documents remarkable increase in endometrial cancer (EC) in 26 of the 43 populations studied during 1978-2013.…”
Section: Endometriosis-associated Extra-ovarian Cancersmentioning
confidence: 58%
“…Although diabetes has long been known to be an independent risk factor for EC, little is known about the relationships between IR and EC [213]. Literature data were unable to indicate clear associations between insulin, IGFs, and sex steroid hormones with EC incidence because of the multitude of dysregulated pathways that lead to EC progression.…”
Section: Perspective and Future Directionsmentioning
confidence: 99%
“…The post-WHI analysis [54] discovered a high incidence of endometrial cancer [55], specially an increase over time in women aged 50-74 years (with an annual percentage change, in 2004-2009: 2.8%; in 2005-2009: 3.3%; and 2006-2009: 4.2%) [56], parallel to the decrease in the use of FDA-approved estrogen plus progestogen HT and parallel to the increase of endometrial hyperplasia [57], and after the increasing usage of compounded bioidentical HT (CBHT) instead of pharmacological products [58,59], even if CBHT are not approved by the FDA, because both hormone compounds lack of standard [type (estrogen: is E2 or E3), dosage, (under dosage), and underpotency (for progesterone)] [60].…”
Section: Endometrial Safety On Mht: History Regimens Endometrial Asmentioning
confidence: 99%